The The Role of Communication on Juvenile Delinquency in Social Learning Perspective: The Role of Communication on Juvenile Delinquency in Social Learning Perspective - Kusnul Khotimah; Deki Wibowo; Katon Galih Setyawan (Metafora: Education, Social Sciences and Humanities Journal, 2022)
Abstract Juvenile delinquency is not a new thing in the social life of society, but juvenile delinquency cases are still interesting to be discussed anytime and anywhere. Juvenile delinquency is a form of self-actualization of a child out of the rules or norms that apply in the family and society in their social environment. The juvenile delinquency paradigm is broader in scope and deeper in content. Juvenile delinquency includes actions that often cause unrest in the community, school and family environment. The city of Blitar is also known as the little kutha kang kawentar. The students at MTsN Kepanjenkidul in Blitar City are all Muslim, but they have not fully implemented the attitudes and examples that have been applied in schools. This research method uses a qualitative approach. This primary data was obtained through interviews and field observations. Furthermore, secondary data obtained from primary data. In this study, the researcher acts as an instrument as well as a data collector. The procedure used in data collection, namely in-depth interviews. The interviews conducted were unstructured and open-ended interviews using interview guidelines that had been compiled. Researchers used non-formal visits to informants' homes. Thus the data obtained are in accordance with the answers and information desired, both by informants and researchers during the interview process. The results of the study indicate the importance of improving the quality of parent-child communication because juvenile delinquency is closely related to the family, one of which is the quality of the relationship with parents. High quality relationships can be seen from warmth, acceptance, and protection. Quality relationships not only inhibit problem behavior, but also reduce the incidence of anxiety, depression, and psychological stress. This is in accordance with Bandura which states that the quality of communication between parents and children with problems has a very large impact on one's behavior because one can learn everything from the observations of others (observational learning). Keywords: communication, juvenile delinquency, and social learning